2022
DOI: 10.1039/d2qi00513a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of cucurbit[n]uril-based supramolecular frameworks via host–guest inclusion and functional properties thereof

Abstract: Frameworks utilizing cucurbit[n]uril-based chemistry build on the rapid developments in the fields of metal-organic frameworks (MOFs), covalent-organic frameworks (COFs), and supramolecular organic frameworks (SOFs), and as porous materials have found...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 159 publications
0
53
0
Order By: Relevance
“…154 Importantly, Huang, Yang and others have reported that MIMs and supramolecular polymers based on Q[n]s can be envisioned in practical applications such as pharmaceutical science [155][156][157] and functional material science. [158][159][160][161][162][163][164][165][166][167][168][169]…”
Section: Chem Soc Revmentioning
confidence: 99%
“…154 Importantly, Huang, Yang and others have reported that MIMs and supramolecular polymers based on Q[n]s can be envisioned in practical applications such as pharmaceutical science [155][156][157] and functional material science. [158][159][160][161][162][163][164][165][166][167][168][169]…”
Section: Chem Soc Revmentioning
confidence: 99%
“…By rational design of the ligands, SOFs not only can exhibit good structural periodicity, but also show broad applications in sensing, separation and environmental fields. 76,77…”
Section: D-sofs Based On Macrocyclic Hostsmentioning
confidence: 99%
“…In the course of our ongoing studies on Q[n]-based coordination polymers, we have been interested in Q[n] derivatives and new types of organic aromatic molecules containing different functionality. 26 Symmetrical tetramethylcucurbit [6]uril (TMeQ [6]), a derivative of Q [6], possesses an ellipsoidal hydrophobic cavity and exhibits moderate solubility in aqueous media. 21 4,4′-Biphenyldisulfonic acid (H 2 BPDS) is an organic aromatic molecule with two sulfonic groups located at its ends.…”
Section: Introductionmentioning
confidence: 99%